Input-Specific GABAergic Signaling to Newborn Neurons in Adult Dentate Gyrus - Markwardt, Sean J. (Society for Neuroscience, 2009)
Adult neurogenesis is the multistage process of generating neurons from adult neural stem cells. Accumulating evidence indicates that GABAergic depolarization is an important regulator of this process. Here, we examined GABAergic signaling to newly generated granule cells (GCs) of the adult mouse dentate gyrus. We show that the first synaptic currents in newborn GCs are generated by activation of GABA(A) receptors by GABA with a spatiotemporal profile suggestive of transmitter spillover. However, the GABAergic response is not attributable to spillover from surrounding perisomatic synapses. Rather, our results suggest that slow synaptic responses in newborn GCs are generated by dedicated inputs that produce a relatively low concentration of GABA at postsynaptic receptors, similar to slow IPSCs in mature GCs. This form of synaptic signaling drives robust phasic depolarization of newborn GCs when the interneuron network is synchronously active, revealing a potential mechanism that translates hippocampal activity into regulation of adult neurogenesis via synaptic release of GABA.